Identifikasi Mutu Fisik Dan Fisiologis 16 Genotip Benih Calon Tetua Jagung Manis Hibrida Unpad setelah 2 dan 4 Bulan Penyimpanan - Debby Yolanda Sulista; Anne Nuraini; Muhamad Kadapi (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Hybrid seed is not always have good longetivity. Therefore, breeder should select longetivity character from parental lines to get hybrid with longetivity characeter. Longetivity character can be revealed by physical and physiological identification of seed. The aim of this research was to identify physical and physiological of 16 parental lines genotypes of sweetcorn after storage. The experimental design in this research used Randomized Complete Design. The treatment in this reserach used 16 Unpad sweet corn parental lines with two replications. The data were analyzed using the F test, Scott Knott 5%, and Duncan 5%. The results showed that there were significant differences in seed electrical conductivity, germination capacity, vigor index, normal seedling dry weight and 100 seeds weight , and seed growth simultaneously at 2 month storage, and normal seedling dry weight and 100 seeds weight at 4 month storage. The best genotypes after storage was 578 which was from P parent, according to the delta value of seed quality changed.